2009
DOI: 10.1590/s0366-69132009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Remoção de cádmio a partir da argila de Toritama (estado de Pernambuco) ativada termicamente em sistema de banho finito

Abstract: ResumoEste trabalho tem como objetivo caracterizar a argila de Toritama, estado de Pernambuco, na sua forma "in natura" após ativação térmica a 500 °C visando sua utilização na remoção de Cd 2+ . A argila "in natura" foi caracterizada por meio de espectrometria de raios X por energia dispersiva (EDX), difração de raios X e análise textural usando adsorção física de nitrogênio (BET). As argilas ativadas termicamente (100, 200, 300, 400 e 500 °C) foram caracterizadas por difração de raios X. A argila ativada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
10
28
0
1
Order By: Relevance
“…Thus, it is possible to observe the presence of montmorillonite and quartz, typical of this type of clay whereby smectite is the predominant clay mineral (SOUZA SANTOS, 1992). Thermal treatment caused distortions in the crystalline structure modifying thus the Bragg reflection standards, calcination may be followed by cation movement within the octahedral sheet (BOJEMUELLER et al, 2001).…”
Section: Results and Discussion Ph Zpc And Zinc Speciationmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is possible to observe the presence of montmorillonite and quartz, typical of this type of clay whereby smectite is the predominant clay mineral (SOUZA SANTOS, 1992). Thermal treatment caused distortions in the crystalline structure modifying thus the Bragg reflection standards, calcination may be followed by cation movement within the octahedral sheet (BOJEMUELLER et al, 2001).…”
Section: Results and Discussion Ph Zpc And Zinc Speciationmentioning
confidence: 99%
“…Thermal treatment caused distortions in the crystalline structure modifying thus the Bragg reflection standards, calcination may be followed by cation movement within the octahedral sheet (BOJEMUELLER et al, 2001). The contaminated clay has a mangling of peak d(001) due to Zn The adsorption of zinc ions into clay pores occurs rapidly at the first moments of the process where there are a lot of empty sites for adsorption, and over time, the number of empty sites decreases and favors the action of repulsive forces of molecules already adsorbed zinc, which complicates the process of adsorption by the remaining sites (STATHI et al, 2007). The maximum adsorbed amount was 4.95 mg metal g (b)Effect of initial solution pH Several studies such as Abollino et al (2008), Chen et al (2008, Arias and Sen (2009) observed that the solution pH is an important parameter in the adsorption of metal ions on clay.…”
Section: Results and Discussion Ph Zpc And Zinc Speciationmentioning
confidence: 99%
See 1 more Smart Citation
“…Este estudo, assim como outros trabalhos que vem sendo desenvolvidos no Laboratório de Desenvolvimento de Novos Materiais (LABNOV) na remoção de metais pesados (Rodrigues, 2003;Silva et al, 2009;Lima et al, 2011;Patrício, 2012;Mota, 2013;Cunha et al, 2014;Cunha et al, 2016;LIMA et al, 2012;Silva et al, 2015), foi realizado para caracterizar a argila Chocolate B natural e modificada termicamente a 500 ºC por meio das técnicas de difratometria de raios X (DRX), capacidade de troca de cátions (CTC) e adsorção física de nitrogênio, visando sua utilização como adsorvente no processo de remoção de chumbo por meio de ensaios de banho finito. Foi realizado um planejamento experimental fatorial 2 2 com triplicata no ponto central, totalizando 7 experimentos analisando-se os fatores pH (3, 4 e 5) e concentração inicial de metal (10, 30 e 50).…”
Section: Introductionunclassified
“…Owing to their adsorption capacity, aluminosilicate and oxide minerals are capable of removing many metals from soil, aqueous solutions and waste waters (ÁLVAREZ-AYUSO; GARCIA-SÁNCHEZ, 2003) over a wide pH range. Then, clay minerals like bentonite, vermiculite and illite (BEREKET et al, 1997;LACIN et al, 2005;MELLAH;CHEGROUCHE, 1997;RODRIGUES et al, 2004;SANTOS et al, 2002;SILVA et al, 2009) and Fe oxide minerals such as goethite (MUSTAFA et al, 2004), have been extensively used for metal removal. The process involves precipitation, ion exchange and adsorption.…”
Section: Introductionmentioning
confidence: 99%